Rhetorical moves structure employed in the research article abstracts: A genre analysis - Presto, Mary Donnabelle; Culajara, Khareen (UM Digos Research Journal, 2016)
Writing in academic genre is the most challenging part of the non-native student writers. Research article abstract have been a growing research in the past two decades. Thus, the aim of the present study was to examine and investigate the rhetorical moves employed in the research article abstracts. This study utilized Bhatia (1993), Santos (1996) and Hyland (2003) models of rhetorical moves of abstract written by the undergraduate students under the Liberal Arts departments of UM Digos College during the year 2017-2014. The results shows that there were 15 move patterns found in the 29 research articles abstracts being examined and none of the 15 move patterns were compatible with Bhatia (1993), Santos (1996) and Hyland (2003) models of rhetorical moves of abstracts. This given the idea that the Liberal Arts department thesis abstracts do not follow or adopt any of the three influential people in the researches of abstracts. Ergo, the findings of the present study have pedagogical implication that the non-native student researchers need to realize the importance of applying any of the three proposed theory of the rhetorical move structure of abstracts by Bhatia (1993), Santos (1996), Hyland (2003) in their abstracts writing since these model’s convey important information that should be available in the research abstracts.